ANALISIS STUDI KRITIS BAHAN AJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM MATERI HUKUM HALAL DAN HARAM KELAS VI DI SD SWASTA MANAN JAYA - Nura Nur’aeni; Siti Qomariyah; Eni Nuraeni; Arif Saipullah; Deliyanti Dimyati (STKIP Subang, 2026)
This study aims to critically analyze Islamic Religious Education teaching materials on the topic of halal and haram laws for sixth-grade students at SD Swasta Manan Jaya. The study is motivated by the importance of teaching materials that not only deliver knowledge but also shape students’ attitudes and behaviors based on Islamic values. This research uses a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation of the teaching modules. Data analysis follows the Miles and Huberman model, including data reduction, data display, and conclusion drawing.The results show that the teaching materials have covered key learning components, including objectives, content, methods, evaluation, and learning resources. However, several weaknesses were identified, such as learning objectives that are not yet operational and measurable, less contextual materials, teaching methods that do not fully encourage student engagement, and evaluation that is not fully based on authentic assessment. Therefore, more innovative, contextual, and HOTS-oriented teaching materials are needed to enhance meaningful learning.